Level Of Corporate Social Disclosure In Malaysia. - Haron, Hasnah; Yahya, Sofri; Chambers, Andrew; Manasseh, Sharon; Ismail, Ishak (2004)
The research examines the level of corporate social disclosure among Malaysian listed companies during the period of recession of financial crisis and also during the pre and post financial crisis periods